Self-reported diabetes mellitus and its association with overweight in the older adults. 10.5007/1980-0037.2011v13n6p442 - Andreia Pelegrini; Raildo da Silva Coqueiro; Edio Luiz Petroski; Tania Rosane Bertoldo Benedetti (Universidade Federal de Santa Catarina, 2011)
This study aimed to identify the prevalence of self-reported diabetes mellitus in the older adults in Florianopolis and its relationship with being overweight. 857 older adults took part in the study. Sociodemographic (sex, age group, schooling, monthly income), anthropometric (weight, height), usual physical activity, arterial hypertension and diabetes mellitus information was collected. The Body Mass Index (BMI) was adopted to diagnose the overweight. The adjustment variables were: sociodemographic, usual physical activity and arterial hypertension. The prevalence of diabetes mellitus was 13.5% (male = 12.1%; female = 14.8%; p<0.05) and the overweight was 59.4% (male = 58.0%; female = 60.7%; p=0.40). A higher prevalence of diabetes mellitus was observed in the older adults who were overweight. The overweight was positively associated with diabetes, regardless of sex, age, schooling, monthly income, usual physical activity and arterial hypertension. One can conclude that overweight in the older adults in Florianopolis was an independent factor and positively associated with diabetes mellitus.